OVERCOMING INFEASIBILITY IN BCC MODELS UNDER DELETED DOMAIN, WITH AN APPLICATION. - Santos, Jorge (2018)
It is a well-known fact that the Banker Charnes and Cooper models under deleted domain can originate unfeasible linear programs for extreme observations. In this paper, we introduce a way to overcome this issue introducing some extra constraints in the multiplier model. Finally, we apply these models to data of the Spanish hotel industry.